2002
DOI: 10.1152/ajpregu.00241.2001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced endogenous GABA-mediated inhibition in the PVN on renal nerve discharge in rats with heart failure

Abstract: One characteristic of heart failure (HF) is increased sympathetic activation. The paraventricular nucleus (PVN) of the hypothalamus (involved in control of sympathetic outflow) has been shown to have increased neuronal activation during HF. This study examined the influence of endogenous GABA input (inhibitory in nature) into the PVN on renal sympathetic nerve discharge (RSND), arterial blood pressure (BP), and heart rate (HR) in rats with HF induced by coronary artery ligation. In alpha-chloralose- and uretha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
144
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(162 citation statements)
references
References 43 publications
16
144
1
1
Order By: Relevance
“…Similar to previous studies, 4,5,6,22 our data show that BMI microinjected into the PVN in rats infused with vehicle for 7 days significantly increases renal SNA, MAP, and HR. In contrast, rats infused with Ang II had significantly blunted responses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to previous studies, 4,5,6,22 our data show that BMI microinjected into the PVN in rats infused with vehicle for 7 days significantly increases renal SNA, MAP, and HR. In contrast, rats infused with Ang II had significantly blunted responses.…”
Section: Discussionsupporting
confidence: 91%
“…4 Although mechanisms of GABA-Ang II interaction within the PVN have not been fully defined, in vitro electrophysiological studies indicate that GABA tonically opposes excitatory actions of Ang II on neurosecretory neurons, 18 and excitation of spinally projecting neurons involves presynaptic actions of Ang II to reduce GABA release. 19 In addition, functional studies in rats with sodium-dependent hypertension 20 and heart failure 6 have suggested that Ang II-induced sympathoexcitation involves reduced GABA-mediated inhibition within the PVN. This conclusion is consistent with evidence that both plasma Ang II and SNA are elevated whereas the sympathetic response to blockade of PVN GABA-A receptors is attenuated in these disease models.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32). Interestingly, their recent study (45) showed that endogenous GABA effects in the PVN of rats with CHF were reduced. These studies suggest that GABA may be responsible for the sympathoinhibition when NO production is augmented.…”
Section: Discussionmentioning
confidence: 99%
“…Gammaaminobutyric acid (GABA) is the predominant inhibitory neurotransmitter within the PVN (Cole and Sawchenko 2002;Chen et al 2003). Patel et al previously suggested that a GABA-mediated inhibitory mechanism within the PVN contributed to sympathoexcitation in HF rats (Zhang, Li et al 2002). In addition, nitric oxide (NO) levels are inversely related to sympathetic activity and are downregulated in the PVN of HF rats.…”
mentioning
confidence: 99%